Multi-functional nitrogen self-doped graphene quantum dots for boosting the photovoltaic performance of BHJ solar cells. (April 2017) - Moon, Byung Joon; Jang, Dawon; Yi, Yeonjin; Lee, Hyunbok; Kim, Sang Jin; Oh, Yelin; Lee, Sang Hyun; Park, Min; Lee, Sungho; Bae, Sukang
Abstract: The tunable heteroatom doping density in graphene quantum dots (GQDs) can provide unique opportunities for advanced electrochemical and opto-electronic applications with control of intrinsic properties that allow exploiting new phenomena. Herein, we report a facile one-step synthesis of the nitrogen-doped high-crystallinity GQDs (nGQDs) from poly-acrylonitrile (PAN)-based CFs using the solvo-thermal cutting method. Interestingly, the optical properties of nGQDs can be simply controlled by varying the heat treatment temperature of the CFs with different N contents. We also conduct an in-depth study on the optical properties of nGQDs according to the variation of N atom density that can be readily modulated by controlling the graphitization temperature of CFs, via both experimental and computational analyses. The synthesized nGQDs are blended with PEDOT:PSS as an anodic buffer layer to induce efficient hole extraction and energy-down-shift in organic photovoltaic (OPV) devices that provide an enhanced power conversion efficiency (PCE) from 7.5% to 8.5%. Because of the wide absorption band, high carrier extraction, and non-toxicity, these nGQDs are demonstrated to be excellent probes for high-performance opto-electronic applications. Graphical abstract: Highlights: Facile one-step synthesis of the substitutional N-doped GQDs (nGQDs) from PAN-based carbon fibers (CFs), Regulating the concentration of heteroatoms and N-bonding configurations by altering the heat treatment temperature of CFs. As-prepared nGQDs have not only a high degree of optical tunability but also have outstanding crystallinity. Efficient down energy conversion and charge transport have been confirmed.